Perekonomian indonesia pada masa orde lama : antara kebijakan ekonomi dan stabilitas sosial - Effendy, Syazani Azmy (Maliki Interdisciplinary Journal, 2025)
During the Old Order period (1945-1966), young Indonesians were faced with various challenges and political instability in economic development. The economic policies implemented by the government at that time were influenced by efforts to build a newly independent country and strengthen national identity. In the midst of abundant natural resources without being balanced by qualified human resources, the economic system will be less stable. However, during the Old Order era, Indonesia’s economic policies focused on industrialization and nationalization of foreign companies, as well as creating economic independence. However, these policies were often carried out without careful planning, which led to an imbalance between economic needs and social stability. One significant impact was soaring inflation, scarcity of goods, and budget deficits that disrupted people’s welfare. On the other hand, political and social pressures, including ideological conflicts created by bureaucrats between communist, nationalist and Islamic groups, also affected the stability of the country. This article therefore discusses how the economic policies of the Old Order interacted with socio-political dynamics and their impact on the Indonesian economy. With these studies, the aim of this article is to provide a deeper understanding of the relationship between the economic policies adopted by the Old Order government and the efforts to maintain social stability amidst the economic crisis.